Organizational and pedagogical conditions for the determination of gifted children and support policies for effective management in an educational institution - Kozhevnikov, Mihail V.; Lapchinskaia, Irina V.; Korneeva, Natalia Y.; Romanov, Petr Yu.; Uvarina, Natalia V. (Cuestiones Políticas, 2020)
The article describes the organizational and pedagogical conditions for the determination and support of the effective management of gifted children in an educational institution based on personality-oriented educational technologies. The authors pay special attention to determining the research predisposition in the learning process (cognition), which can be considered as the most important form of manifestation of the research position of a gifted child. This position is most clearly expressed in problem situations, suspenseful and unusual situations. The approach to teaching gifted children is not based on the reproductive activity of a student in the assimilation of knowledge, skills, but on a creative search that leads to the development of individual intellectual and creative potential. In the main conclusions, the authors of the article point out the important role of the development of the educational environment, which includes three components: spatial-subject, social and technological. The educational environment must consider the age, gender, national characteristics, level of intellectual and mental development of a student's personality, all of which demands the implementation of a set of public policies in the education sector.